2020
DOI: 10.3390/rs12152376
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing Image Scene Classification with Noisy Label Distillation

Abstract: The widespread applications of remote sensing image scene classification-based Convolutional Neural Networks (CNNs) are severely affected by the lack of large-scale datasets with clean annotations. Data crawled from the Internet or other sources allows for the most rapid expansion of existing datasets at a low-cost. However, directly training on such an expanded dataset can lead to network overfitting to noisy labels. Traditional methods typically divide this noisy dataset into multiple parts. Each part fine-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The discriminative modality distillation approach is introduced in [47], the teacher is trained on multimodal data, and then, the student model learns from the teacher model to improve the performance of the remote sensing image classifications. To address the problem of network overfitting due to noisy data, a novel noisy label distillation method (NLD) is proposed in [48].…”
Section: Knowledge Distillation and Sdmentioning
confidence: 99%
“…The discriminative modality distillation approach is introduced in [47], the teacher is trained on multimodal data, and then, the student model learns from the teacher model to improve the performance of the remote sensing image classifications. To address the problem of network overfitting due to noisy data, a novel noisy label distillation method (NLD) is proposed in [48].…”
Section: Knowledge Distillation and Sdmentioning
confidence: 99%
“…Discriminative modality distillation approach is introduced in [48], the teacher is trained on multimodal data and then the student model learns from the teacher model to improve the performance of the RS image classifiction. To address the problem of network overfitting due to noisy data, a novel noisy label distillation method (NLD) is proposed in [49].…”
Section: Knowledge Distillation and Self-distillationmentioning
confidence: 99%
“…In the early stage of development, traditional machine learning methods have been used for scene classification tasks, such as support vector machine and bag of words [2,3]. Recently, deep learning methods have been proven to be effective for extracting image features [4][5][6][7][8], and many studies have demonstrated effective scene classification performance with the help of deep learning from various novel perspectives including self-supervised learning [9], data augmentation [10], feature fusion [11][12][13][14][15], reconstructing networks [16][17][18][19][20][21][22][23], integration of spectral and spatial information [24], balancing global and local features, refining feature maps through encoding method [25], adding a new mechanism [26,27], as well as introducing a new network [28], open set problem [29], and noisy label distillation [30]. However, a lack of annotated data has restricted the development of deep learning methods in scene classification due to the high cost of annotating data.…”
Section: Introductionmentioning
confidence: 99%